LCS Approach to Tasks Scheduling Problem in the Two Processor System - Wasilewska, Katarzyna; Seredyński, Franciszek (Studia Informatica. System and information technology, 2007)
In this paper we propose an approach to solve multiprocessor scheduling problem with use of rule-based learning machine – Learning Classifier System (LCS). LCS combines reinforcement learning and evolutionary computing to produce adaptive systems. We interpret the multiprocessor scheduling problem as multi-step problem, where a feedback is given after some number steps. We show that LCS is able to solve scheduling tasks of a parallel program in the two processor system.